Indonesia`s Perspective On World Trade Organization (WTO) Moratorium On Customs Duties On Electronic Transmission: A Brief Review Of Literature - Hidayat, Achmad; Nainggolan, Yoko Agustwen Shinta Uli; Pamutra, Gilang Rizki (Politeknik Keuangan Negara STAN, 2023)
In 1998, the World Trade Organization (WTO) has announced a moratorium on customs duties on electronic transmissions, which has led to lengthy debates about whether to include electronically transmitted content. This study was carried out to ellaborate and emphasize the Indonesian Government persepective on the moratorium customs duty. This descriptive qualitative study conducted in several methods such as literature review, meeting informants in the field, and conducting interviews and observations mainly in the Directorate General Customs and Excise of the Republic of Indonesia. Currently, Indonesian Customs Law has stipulated that â€œdigital goodsâ€ are objects of the Customs Law and Indonesia has been imposing most favoured nation (MFN) tariff of zero percent (0%) on software and other digital goods (HS 99.01). The rationales of imposing customs duties on digital goods are not solely about the state revenue, but there are several rationales, namely recording data statistic, creating level of playing field, encouraging local SMEs, providing business certainty, and assessing digital goods risks. In conclusion, Indonesia Government suggested that WTO Members consider to analyze this moratorium implementation from a holistic perspective and also need to be equipped with crucial elements, such as a multilaterally- agreed scope, definition, and impact of the moratorium.Â Therefore, the discussion regarding the moratorium should be intensively conducted in the WTO Work Programme of E-Commerce.